Association of stress and emotional eating on the nutritional status of college students in Indonesia: A narrative review - Arny Alfinda (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Emotional eating is the tendency to overeat in response to negative emotions. Students with high academic demands experience changes in eating patterns, low physical activity, and emotional eating behaviors that can affect nutritional status. Purpose: To analyze the relationship between stress and emotional eating on the nutritional status of students in Indonesia. Method: This study analyzed 10 articles based on original research in cross-sectional studies published between 2020 and 2025, obtained from several electronic databases such as Google Scholar and GARUDA. The selected studies included variables related to stress, emotional eating habits, and the relationship between these factors was tested and statistically proven. Results: Emotional eating patterns and stress do not directly affect nutritional status but can act as risk factors when interacting with insufficient physical activity and excessive energy intake, particularly carbohydrates and fats. Stress is correlated with disrupted eating behavior and influenced by emotion-dependent eating patterns, but its impact on nutritional status may be masked by other factors such as physical activity and genetics. Conclusion: Strong evidence from several studies indicates a relationship between stress, emotional eating, and nutritional status among college students in Indonesia. Keywords: College Students; Emotional Eating; Nutritional Status; Stress.